Argonauta nodosa Solander, 1786 (Cephalopoda: Argonautidae) in argentine waters - Pastorino, Roberto Santiago Guido (2002)
Argonauta nodosa Solander, 1786 is formally recorded off Puerto Quequén, in the south of Buenos Aires province, Argentina. Despite some scanty dubious citations in early local malacological literature this is the first record from Argentine temperate waters. Two females were collected from the stomach contents of the blue shark Prionace glauca and one empty egg case was recovered by fishermen nets. Two other lots were found in museum collections. Morphological data on the animal, shell and beaks are provided. Some remarks are pointed out about the presence of this worldwide tropical species.